INCREASING STUDENT’S VOCABULARY OF THE FIRST GRADE AT SMA NEGERI 3 TOLITOLI THROUGH WORDS ASSOCIATION GAME - Moh Firmansyah (Universitas Madako Tolitoli, 2019)
The objective of the research is to find out whether the application words association technique increasing students’ vocabulary words association game or not. It is a True-Experimental research. It is conducted at first grade of SMA Negeri 3 Tolitoli that was (X MIA1). The writer gave a pre-test to measure the students previous ability in vocabulary words association after given treatment which is the application of words association game technique. The writer used SPSS 16.0 program to analyze the data collection. the result of data analysis showed that technique give a significant effect to the students’ in words association game. The mean score of the post-test (80,61) was higher than the mean score of pre-test (63,65). Then, the testing hypothesis showed that the value of tcount (tc) was greater than ttable (tt) (6.099 ≥ 2,017). In conclusion, The application of words association game technique is effective to increasing students’ vocabulary.Keywords: Increasing, Vocabulary, Words Association Game, Experiment